ANALISIS LIKUIDITAS, SOLVABILITAS DAN AKTIVITAS DALAM MENGENDALIKAN PROFITABILITAS PADA PT INDOMOBIL SUKSES INTERNASIONAL, Tbk YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rizki Kurniawan; Yansen Siahaan; Ady Inrawan; Ernest Grace (JURNAL AKUNTANSI FINANCEIAL STIE SULTAN AGUNG, 2019)
The purpose of this research is to description of liquidity, solvability, activity and profitability and to know what factors cause the profitability of PT Indomobil Sukses Internasional, Tbk which are listed on the Indonesia Stock Exchange tend to decrease. The research was using qualitative desriptive analysis. The data collection was using documentation. The analysis techniques used are qualitative descriptive analysis methods and inductive analysis.The result of this research are Current Ratio (CR) tends to decrease, Debt to Asset Ratio (DAR) tends to increase,Total Asset Turn Over (TATO) tends to decrease and Return on Assets (ROA) tends to decrease. The factors that cause decreased profitability are receivables, inventories, payables, long-term bank loans that are due soon, bank debt and sales.The suggestion of this research is that it is better to issue new debt, namely long-term debt used to pay off short-term debt, consider continuing or stopping the segment of commercial vehicle sales and passengers with certain product brands that experience continuous losses, managing inventory to increase sales.Keywords: Liquidity, Solvability, Activity and Profitability